전단코팅 공정으로 제조하는 금속-할라이드계 페로브스카이트의 박막성장에 미치는 공정변수의 영향 고찰 - 최지혜(Jihye Choe); 송지호(Jiho Song); 정지영(Jiyoung Jeong); 정중희(Choong-Heui Chung); 김재균(Jaekyun Kim); 홍기하(Ki-Ha Hong) (Biuletyn Uniejowski, 2019)
Metal-halide perovskite (MHP) solar cell is a promising candidate for next-generation flexible devices and the BIPV (Building-integrated photovoltaics) because it can exhibit high power conversion efficiencies over 23%, good bendability and low processing cost. However, MHP solar cells are commonly fabricated by the spin coating that is not a reliable method to produce large-scale commercial solar cells. A shear coating can be one of the potential candidates for the large-scale deposition method of MHP films. In this work, the influences of the process parameters such as solvents of precursor solution, substrate temperature, concentrations of precursor solution, and annealing time on the thin film growth of MHP were investigated for the shear coating process. This study presents the possibility of the shear coating process for large-scaled perovskite film fabrication and reveals the role of process condition in the thin film growth of perovskites.